Altered Soil Properties Inhibit Fruit Set but Increase Progeny Performance for a Foundation Tree in a Highly Fragmented Landscape - Llorens, Tanya M.; Yates, Colin J.; Byrne, Margaret; Elliott, Carole P.; Sampson, Jane; Fairman, Richard; Macdonald, Bronwyn; Coates, David J. (Frontiers in Ecology and Evolution, 2018)
Failing to test multiple or non-standard variables in studies that investigate the effects of habitat fragmentation on plant populations may limit the detection of unexpected causative relationships. Here, we investigated the impacts of habitat fragmentation on the pollination, reproduction, mating system and progeny performance of Eucalyptus wandoo, a foundation tree that is bird and insect pollinated with a mixed-mating system. We explored a range of possible causative mechanisms, including soil properties that are likely to be altered in the agricultural matrix of a landscape that has naturally nutrient-poor soils and secondary soil salinization caused by the removal of native vegetation. We found very strong negative relationships between soil salinity and fruit production, thus providing some of the first evidence for the effects of salinity on reproduction in remnant plant populations. Additionally, we found unexpectedly higher rates of seedling survival in linear populations, most likely driven by increased soil P content from adjacent cereal cropping. Higher rates of seed germination in small populations were related to both higher pollen immigration and greater nutrient availability. Trees in small populations had unexpectedly much higher levels of pollination than in large populations, but they produced fewer seeds per fruit and outcrossing rates did not vary consistently with fragmentation. These results are consistent with small populations having much higher insect abundances but also increased rates of self-pollination, combined with seed abortion mechanisms that are common in the Myrtaceae. This study highlights the need to better understand and mitigate sub-lethal effects of secondary soil salinity in plants growing in agricultural remnants, and indicates that soil properties may play an important role in influencing seed quality.